1995
DOI: 10.1111/j.1476-5381.1995.tb13313.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of different receptor subtypes in the pre‐ and postjunctional actions of angiotensin II at rat sympathetic neuroeffector sites

Abstract: 1 The effects of the nonpeptide angiotensin II receptor (AT) antagonists losartan and PD 123319 on actions of angiotensin II in the rat caudal artery and rat vas deferens preparations were investigated. 2 Angiotensin 11 (1.0 I1M) increased perfusion pressure in isolated segments of the rat caudal artery.This increase in perfusion pressure was prevented by the AT,-antagonist, losartan (0.1 JAM) but was not affected by the AT2-antagonist, PD 123319 (0.1 JAM). 3 Angiotensin II (0.1-3.01M) produced a concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
49
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 25 publications
11
49
0
Order By: Relevance
“…The significantly greater basal luminal perfusion pressure observed in the present study in caudal artery preparations from SH rats compared to that in preparations from WKY rats is consistent with findings with the mesenteric vasculature (Lais & Brody, 1978; tions of angiotensin II in rabbit renal artery (Zhang et al, 1994), rat portal vein, rabbit aorta and pulmonary artery (Rhaleb et al, 1991). Likewise, we previously described blockade by losartan of the vasoconstrictor response to angiotensin II in the caudal artery of Sprague-Dawley rats (Cox et al, 1995 Prejuncdonal anglotensin 11 receptors in SH rats sponse. In preparations from both strains of rats, the maximal enhancement of S-I [3H]-noradrenaline efflux and of the vasoconstrictor response occurred with a concentration of 1 gM and a further increase in concentration to 3 gM produced less enhancement.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The significantly greater basal luminal perfusion pressure observed in the present study in caudal artery preparations from SH rats compared to that in preparations from WKY rats is consistent with findings with the mesenteric vasculature (Lais & Brody, 1978; tions of angiotensin II in rabbit renal artery (Zhang et al, 1994), rat portal vein, rabbit aorta and pulmonary artery (Rhaleb et al, 1991). Likewise, we previously described blockade by losartan of the vasoconstrictor response to angiotensin II in the caudal artery of Sprague-Dawley rats (Cox et al, 1995 Prejuncdonal anglotensin 11 receptors in SH rats sponse. In preparations from both strains of rats, the maximal enhancement of S-I [3H]-noradrenaline efflux and of the vasoconstrictor response occurred with a concentration of 1 gM and a further increase in concentration to 3 gM produced less enhancement.…”
Section: Discussionsupporting
confidence: 80%
“…We have recently found that the enhancement of transmitter noradrenaline release by angiotensin II in the caudal artery of Sprague-Dawley rats is blocked by both losartan and PD 123319 (Cox et al, 1995). Thus, we suggested that the prejunctional receptor subserving the enhancement of transmitter noradrenaline release in this tissue had characteristics similar to the ATIB binding site described by Zhou et al (1993).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations